Machine Learning, Reasoning, and Intelligence in Daily Life: Directions and Challenges - Horvitz, Eric (2007)
Technical developments and trends are providing a fertile substrate for creating and integrating machine learning and reasoning into multiple applications and services. I will review several illustrative research efforts on our team, and focus on challenges, opportunities, and directions with the streaming of machine intelligence into daily life.
Proceedings of the Eighteenth Conference on Uncertainty in Artificial Intelligence, Edmonton, Alberta,